Strategies for Increasing the Use of Rooftop PV in Indonesia - Haryadi, Fajar Nurrohman; Simaremare, Arionmaro Asi; Hakam, Dzikri Firmansyah; Aditya, Indra Ardhanayudha; Haryani, Indri (Universitas Airlangga, 2022)
The current high energy consumption can cause scarcity as Indonesia's population growth has increased quite significantly. Alternative energy is needed to anticipate energy problems in the future. Solar energy is one of the options given the most significant potential for energy produced in Indonesia. This research aims to see the strategies that PLN can do to increase the use of Rooftop PV in Indonesia based on the results of the analysis that has been done. The approach to this research is a qualitative approach with the SWOT and FGD methods. Also, the data used are primary data from survey results on Rooftop PV users in Indonesia. The SWOT analysis results show that PLN is in quadrant I, which means it has an extreme market position. PT PLN has the potential to increase the use of Rooftop PV in Indonesia. Two strategic points can be carried out by PLN, namely, carrying out vertical integration and diversifying conglomerates. Also, the researcher has proposed several alternative strategies, namely the upstream (manufacturing) development plan, the downstream (consumer) development plan, and the internal development plan.